2006
DOI: 10.1080/09712119.2006.9706816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Species and Age on Nutrient Content and in vitro Digestibility of Opuntia spp.

Abstract: Effect of species and age an nutrient content and digestibility a€ Opuntia spp. J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
(5 reference statements)
1
12
1
1
Order By: Relevance
“…The IVDMD was quadratically affected by period, which is in agreement with Pinos-Rodríguez et al . (2006) who found a quadratic effect of growth on IVDMD. Tegegne (2001) found an IVDMD lower than the current values.…”
Section: Discussionmentioning
confidence: 99%
“…The IVDMD was quadratically affected by period, which is in agreement with Pinos-Rodríguez et al . (2006) who found a quadratic effect of growth on IVDMD. Tegegne (2001) found an IVDMD lower than the current values.…”
Section: Discussionmentioning
confidence: 99%
“…Opuntia spp. offer a high water content, high digestibility and significant amounts of energy [7,8]. In cladodes of the spineless cactus, Opuntia ficus-indica, the protein content ranges from 2.8-8% [7][8][9][10], the fat content ranges from 3.9-4.7 g/100 g DM [9] and the content of metabolisable energy ranges from 11.1-11.4 mj/kg DM [10], with some variation according to age and genotype.…”
Section: Introductionmentioning
confidence: 99%
“…offer a high water content, high digestibility and significant amounts of energy [7,8]. In cladodes of the spineless cactus, Opuntia ficus-indica, the protein content ranges from 2.8-8% [7][8][9][10], the fat content ranges from 3.9-4.7 g/100 g DM [9] and the content of metabolisable energy ranges from 11.1-11.4 mj/kg DM [10], with some variation according to age and genotype. Opuntia adapts easily to poor-quality soils, withstands water shortages and high temperatures [11,12], and is widely distributed across Latin America, South Africa and the Mediterranean region [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides their use as food nutrients and forage, the OR cladodes have been well known in traditional medicine on the treatment of a variety of diseases, particularly diabetes and hypercholesterolaemia (Santos‐Zea et al ., ). Previous studies demonstrated that OR cladodes showed high‐nutrient content (Pinos‐Rodríguez et al ., ). Furthermore, Santos‐Zea et al .…”
Section: Introductionmentioning
confidence: 99%
“…Besides their use as food nutrients and forage, the OR cladodes have been well known in traditional medicine on the treatment of a variety of diseases, particularly diabetes and hypercholesterolaemia (Santos-Zea et al, 2011). Previous studies demonstrated that OR cladodes showed highnutrient content (Pinos-Rodr ıguez et al, 2006). Furthermore, Santos-Zea et al (2011) studied the phenolic, flavonoid and antioxidant contents of methanol extracts from OR cladode's flours, while Budinsky et al (2001) proved that the regular ingestion of OR prickly pear is able to significantly reduce the in vivo oxidation injury in a group of patients suffering from familial hypercholesterolaemia.…”
Section: Introductionmentioning
confidence: 99%